Self‐Assemble Polymeric Nanoparticle with GSH Exhaustion for SPECT Imaging–Guided Enhanced Radioisotope Therapy. (10th April 2019) - Tao, Yugui; Ren, Pengfei; Yi, Xuan; Zhou, Hailin; Xiong, Saisai; Ge, Fei; Chen, Lei; Yang, Kai
Abstract: Exploiting biocompatible nanomaterials for cancer theranostics has attracted great attention in recent years. Herein, a multifunctional self‐assembled nanoparticle based on a biocompatible polymer that contains 3‐(4‐hydroxyphenyl) propionic acid N ‐hydroxysuccinimide ester (HOPA) for radiolabeling and piperlongumine (PL) for exhausting endogenous glutathione (GSH) (HOPA‐C18PMH‐PEG/PL) is successfully synthesized. With radionuclide 125 I labeling, SPECT imaging shows high tumor uptake of HOPA‐C18PMH‐PEG/PL after intravenous injection. The in vitro and in vivo combined radioisotope therapy (RIT) and chemotherapy using 131 I‐labeled HOPA‐C18PMH‐PEG/PL is then carried out, achieving synergistic antitumor effect. This is because the reactive oxygen species (ROS) level in the tumor sites of mice treated with 131 I‐labeled HOPA‐C18PMH‐PEG/PL is increased after the exhaustion of GSH by PL. Additionally, such a strategy (exhausting GSH and increasing ROS) induces no obvious toxicity to normal tissue. Therefore, as‐made polymeric nanoparticles exhibit multifunctional properties for SPECT imaging–guided combined RIT and chemotherapy in one system. This finding will further promote polymeric nanoparticle–based RIT of cancer and is expected to be used for future clinical transformation. Abstract : Self‐assembled polymeric nanoparticles (HOPA‐C18PMH‐PEG/PL) with GSH exhaustion and radionuclides labeling are developed for SPECT imaging–guided combined therapy. In vitro and in vivo combined radioisotope therapy and chemotherapy using 131 I‐HOPA‐C18PMH‐PEG/PL significantly inhibit tumor growth after intravenous injection.